Adsorption and transport of imazapyr through intact soil columns taken from two soils under two tillage systems - Porfiri, Carolina; Montoya, Jorgelina Ceferina; Koskinen, William C.; Azcarate, Mariela Pamela (2018)
The objective of this work was to study the sorption and transport of imazapyr (IMZ) in two soils with different physical–chemical properties, subject to long-term conventional tillage (CT) and no-tillage (NT) systems. Sorption was carried out using batch equilibrium method and high performance liquid chromatography analytical routines. Displacement experiments through intact soil cores were done using IMZ as reactive solute and bromide (Br) as non-reactive solute. Equilibrium (CDEeq) and non-equilibrium (CDEnon-eq) transport models (CXTFIT 2.1) were employed to describe the breakthrough curves (BTCs). IMZ was only sorbed by NT soils with Kd values ranging from 0.22 to 1.1 L kg−1 . Clay content, pH and CEC values were the main factors affecting the sorption of IMZ. Miscible displacement studies showed that almost all the soil water was mobile and transport was related to physical equilibrium conditions. Some evidence of sorption non-equilibrium was seen in column experiments with IMZ; retardation factors were close to one, demonstrating the low sorption and the high potential to leach of this compound.